FINANCING OF CULTURE FROM LOCAL GOVERNMENT BUDGETS IN POLAND IN THE YEARS 2000-2010 VERSUS THE PERFORMANCE BUDGETING METHOD - Suchecki, Adam Mateusz (European Scientific Journal, ESJ, 2014)
Decentralization of public finance in Poland was an important element of changes in the political system of the country. As a result, some tasks of the state were transferred to the local government level. The Public Finance Act of 2009 introduced new public management methods, such as the performance-based budget and the long-term financial forecast, to the local government finance management. The purpose of this paper was to analyse the budget expenses on cultural tasks incurred by local government units in Poland in the years 2003- 2010 and the impact of the attempted application of the performance budgeting method to local government expenses relating to this field of economy.